Indeks Harga Ekspor, Inflasi, Pengangguran Serta Pengaruhnya Terhadap Pendapatan Nasional Indonesia dan Korea - Bagja Kurniawan; Shafira Restia Sunarya; Frisma Naofal; Gugum Mukdas Sudarjah (Jurnal Riset Ilmu Ekonomi, 2021)
Both developed and developing countries have contributed to the world economy. The level of welfare of a country can be achieved by dynamic economic growth, which is a condition that describes an increase in the GDP of the people of a country. GDP is the value of goods and services in a country produced by the production factors belonging to that country's citizens and foreign countries. GDP growth from year to year is affected by various factors with their respective portions. This study aims to determine the factors that affecting GDP in Indonesia and Korea which were analyzed using multiple linear regression analysis. The test methods we used include the coefficient of determination (R2), F statistical test (simultaneous test) and t statistical test (partial test). There are three independent variables, Total Unemployment, Inflation, and Export Value Index, and the dependent variable is GDP. And the results show that Unemployment variable and Export Value Index have a partially significant effect on GDP and Inflation variable has no partial effect on GDP in Indonesia. Meanwhile in Korea, Unemployment and Inflation have no partial effect on GDP and the Export Value Index has a partially significant effect on GDP.